2017
DOI: 10.1007/s10439-017-1815-7
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Mouse Primordial Germ Cells into Functional Oocytes In Vitro

Abstract: Various complex molecular events in oogenesis cannot be observed in vivo. As a bioengineering technique for female reproductive tissues, in vitro culture systems for female germ cells have been used to analyze oogenesis and preserve germ cells for over 20 years. Recently, we have established a new methodological approach for the culture of primordial germ cells (PGCs) and successfully obtained offspring. Our PGC culture system will be useful to clarify unresolved mechanisms of fertility and sterility from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…Using a stereomicroscope, we dissected the embryos and collected the gonads attached to the mesonephros, which were removed from the gonad using tungsten needles just before the seeding of the gonad. Our culture method for the ovary was based on the protocol described previously by Morahaku et al 26 , 72 . However, in order to perform in-depth cytological, in situ immunofluorescence, and mitochondrial activity studies, we modified the method of the culture procedure depending on the process to be evaluated—follicular progression, immunofluorescence, or mitochondrial activity.…”
Section: Methodsmentioning
confidence: 99%
“…Using a stereomicroscope, we dissected the embryos and collected the gonads attached to the mesonephros, which were removed from the gonad using tungsten needles just before the seeding of the gonad. Our culture method for the ovary was based on the protocol described previously by Morahaku et al 26 , 72 . However, in order to perform in-depth cytological, in situ immunofluorescence, and mitochondrial activity studies, we modified the method of the culture procedure depending on the process to be evaluated—follicular progression, immunofluorescence, or mitochondrial activity.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that mouse fetal gonads cultured in medium containing fetal bovine serum (FBS) exhibited MOF and/or an absence of follicular compartmentalization despite the development of a large number of growing oocytes. As a result, secondary follicles could not be isolated from these ovaries ( Morohaku, 2019 ; Morohaku et al, 2016 , 2017a ). RNA-seq analysis showed that the estrogen-signaling pathway is excessively activated in in vitro -differentiated ovaries compared with in vivo -derived ovaries before follicle formation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been no subsequent reports on the production of porcine chimeras. Most iPSC lines fulfilled the criteria of pluripotency, but the cells could not contribute to chimeras or generate cloned piglets [56][57][58][59][60] .…”
Section: Derivation Of Pluripotent Stem Cells From Primordial Germ Cellsmentioning
confidence: 99%